A Quantitative Framework for the Evaluation of Agile Methodologies - Mendes Calo, Karla (2010)
The methodologies for agile software development are fundamentally based on the collaboration with software users during the entire development process, the simplicity to adapt the product to changes in requirements, and on the incremental product delivery. Based on the Agile Manifesto, they have been accepted and are successfully used in projects where the detailed requirements are unknown at first and are identified during the development process from the interactions with the users and the feedback thus obtained. In this paper, we propose an evaluation framework for the methodologies for agile software development. This framework is applied in detail to two of them -Scrum and eXtreme Programming (XP). The definition of this quantitative framework is innovative, especially because it allows the evaluation of how the agile methodologies satisfy the basic principles defined by the Agile Manifesto, thus it can be used when deciding which methodology to adopt in a particular project.